Zakat, Trust, and the Digital Window: A Comparative Analysis of Web Disclosure Practices Among Indonesia's National Zakat Institutions - Hanifah Permatasari; Liana Trihardianingsih; Eko Purwanto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The National Zakat Amil Institutions (LAZNAS) play a vital role in Indonesia's zakat ecosystem as independent non-governmental organizations connecting muzakki with beneficiaries nationwide, and official websites have become a primary medium through which they communicate identity, programs, and fund management accountability to the public. This study examines digital disclosure patterns across all 15 nationally licensed LAZNAS websites through qualitative content analysis conducted in June 2026, using a five-dimensional rubric adapted from global NPO web disclosure frameworks and enriched with Islamic accountability principles. Findings reveal considerable variation across dimensions and websites, with program reporting the most consistent and financial transparency the most varied. A fund efficiency summary is not yet explicitly available on any website in the sample, reflecting the absence of sectoral norms or regulatory provisions encouraging this type of public digital disclosure, and more than half of the websites face technical barriers that limit public accessibility. The study proposes technical website accessibility as a distinct analytical dimension in Islamic philanthropy web disclosure research and identifies innovative practices with potential for broader sectoral adoption.